ANALISIS PENGARUH PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN IKAN BANDENG (Chanos chanos) DI KECAMATAN SERUWAY KABUPATEN ACEH TAMIANG - Mutia Ardini; Cut Gustiana; Silvia Anzitha (Jurnal Inovasi Penelitian, 2022)
This study aims to analyze influence of consumer preferences for purchasing decisions of milkfish (Chanos chanos) in Seruway District, Aceh Tamiang Regency. The independent variables used in this study are price, location and quality. While the dependent variable used is consumer preferences for milkfish purchasing decisions. Determination of the sampling technique using the Nonprobability Sampling method, namely the saturated sampling method as many as 35 respondents. The data used are primary data and secondary data with a quantitative descriptive approach. Data analysis includes income analysis and multiple linear regression. The results showed that the price variable (X1) had a significant effect on consumer preferences on milkfish purchasing decisions (Chanos chanos), the location variable (X2) had no significant effect on consumer preferences on milkfish purchasing decisions (Chanos chanos), quality variable (X3) has a significant effect on consumer preferences on purchasing decisions of milkfish (Chanos chanos) in Seruway District, Seruway Regency.